Trajectories of Memory Excavating the Past in Indonesia - Budianta, Melani; Tiwon, Sylvia (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book is a collection of essays in Indonesian history and archaeology dealing with different and multiple trajectories, along four broad themes. The first part of the book covers competing or evolving representations of events, customs or traditions, and historical personae in Indonesian official and popular expression, as they are shaped by economic, political, and cultural forces. The second part deals with memories of war and peace, examining transnational conflict and collaboration, the role of political elites and state projects dealing with the aftermath of military aggression, while also focusing on the impact and responses of civilians. The third part focuses on how state and civil societies frame historical figures, in ways that transcend the dichotomy of heroes and victims. The fourth part of the book looks at the way Indonesian museums and museology serve as sites where new kinds of memory work occur, in a post-1998 era. The book is designed with the aim ofclearing a space for a plurality of memory works. Discussions in this volume extend from Loloda island in Eastern Indonesia, to Sabang island at the north westernmost end of the archipelago, and to the cosmopolitan centers. Temporally, it covers the colonial, the post-independence and contemporary eras. By juxtaposing diverse works, the book offers a new vista of multiple trajectories of memory being traced out in and about Indonesia. This is an open access book. Melani Budianta is Professor of literature and cultural studies, Faculty of Humanities, Universitas Indonesia. She has a scholarly interest in the politics of representation, gender, power and cultural diversity. She has done transdisciplinary work in cultural commoning with cultural activists in Indonesia. Sylvia Tiwon is Associate Professor of South and Southeast Asian Studies, University of California, Berkeley. She teaches literature, gender, oral and cultural studies of Southeast Asia with a focus on Indonesia. Her areas of interest include national and pre-national literature, oral discourse and mythologies, as well as socio-cultural formations.